Il valore intrinseco della biodiversità - Matteo Andreozzi (Rivista di Estetica, 2015)
The main aim of this paper is to explore the legitimacy and the implications of ascribing intrinsic value to biodiversity. Several environmental problems are seriously undermining the traditional belief that the moral community should be restricted to human beings only. In this context, the notion of “biodiversity” offers an extremely urgent and inspiring call for philosophical research. Nevertheless, some environmental ethicists still claim that biodiversity has no intrinsic value. I show that the concept of “intrinsic value” has different meanings, depending on their epistemological, ontological, axiological, and normative bases. I argue that while biodiversity has no value in its own right, in itself, or for its own sake, it can be regarded as having value as such. I also claim that ascribing intrinsic value to biodiversity allows a true reconciliation between anthropocentric interests and the need to extend the moral community beyond humanity.